Ալ-Մակրիզիի պատմագրական ժամանակագրությունը - Գագիկ Դանիելյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Таки ал-Дин Ахмад ибн Али ал-Макризи (ум. 1442) - один из выдающихся представителей арабской историографии эпохи Мамлюков. Он родился в Каире в академической семье сирийского происхождения. Полагается, что ал-Макризи имел намерение сочинить всеобщую историю Египта, начиная с мусульманского завоевания до времени своей жизни в трилогии. К сожалению, первая часть этой трилогии (Idq gawahir al-asfat fimuluk Misr wa al-Fustat), по истории от мусульманского завоевания вплоть до начала правления Фатимидов, утрачена. Однако, сохранены две другие части, охватывающие историю Фатимидов (Ittiaz al-hunafa’ bi ahbar al-aimma al-Fatimiyyin al-hulafa), Айюбидов и Мамлюков (Kitab al-suluk limarifat duwal almuluk). Taqi al-Din Ahmad ibn 'All al-Maqrizi (d. 1442) is one of the foremost representatives of Arabic historiography of the Mamluk epoch. It is believed that al-Maqrizi had an intention to compose a comprehensive history of Egypt since the Muslim conquest until his own day in a trilogy. Unfortunately, the first part of it ('Idq gawahir al-asfat fi mulukMisr wa al-Fustat) dealing with the history from the Muslim conquest up to the rule of the Fatimids is now lost. However, preserved are the two other parts covering the history of Fatimid (Itti'azal-hunafa։ bi ahbar al-a’imma al-Fatimiyyin al-hulafa), Ayyubid and Mamluk dynasties (Kitab al-suluk li marifat duwal al-muluk).
Keywords: History; Auxiliary Sciences of History; Medieval History; Chronology; Calendar